"A House of Cards Which Would Not Stand": James Headlam-Morley, the Role of Experts, and the Danzig Question at the Paris Peace Conference*. Issue 2 (3rd April 2019) - Kaufman, D. B.
ABSTRACT: Recent years have witnessed increasing interest amongst international historians on the influence by experts on foreign policy decision making. Most work thus far has concentrated on American foreign policy since 1945, but this analysis broadens the focus to consider the impact of experts on British decision makers through the use of informal networks below the level of Cabinet ministers whilst debating the future of the city of Danzig at the Paris Peace Conference of 1919. It shows that despite a tendency by the protagonists to interpret their actions as subverting the official role and function of the Foreign Office, sufficient evidence can be found to suggest that through the use of back-channels to David Lloyd George, the prime minister, via Philip Kerr, his private secretary, some officials, such as James Headlam-Morley, within the Office managed to influence high-level decision making at Paris.